2023
DOI: 10.1186/s12876-023-02655-0
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic significance of serum CA125 in the overall management for patients with gastrointestinal stromal tumors

Abstract: Background Carbohydrate antigen 125 (CA125) is elevated as a tumor marker in many carcinomas, but its association with gastrointestinal stromal tumor (GIST) has received less attention. This study intends to evaluate whether CA125 level can predict tumor progression and overall survival (OS) of GIST patients. Methods We retrospectively analyzed the clinical data and follow-up records of GIST patients who underwent surgical resection in Nanjing Drum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The expression of ALB and TP, recognized as relevant proteins for monitoring nutritional status, was lower in the GST group than in the other two groups, which is consistent with other cancers. Serum CA125 is elevated in a variety of tumors and plays a key role in the diagnosis of gastrointestinal malignancies (30), but it has not received widespread attention and use in the diagnosis of GIST. Numerous studies have con rmed the correlation between the neutrophil-tolymphocyte ratio (NLR) in cardiovascular diseases, infections, in ammatory diseases and cancer (31,32), but no study has yet singled out LYM% or a potential association between LY and GIST, which is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ALB and TP, recognized as relevant proteins for monitoring nutritional status, was lower in the GST group than in the other two groups, which is consistent with other cancers. Serum CA125 is elevated in a variety of tumors and plays a key role in the diagnosis of gastrointestinal malignancies (30), but it has not received widespread attention and use in the diagnosis of GIST. Numerous studies have con rmed the correlation between the neutrophil-tolymphocyte ratio (NLR) in cardiovascular diseases, infections, in ammatory diseases and cancer (31,32), but no study has yet singled out LYM% or a potential association between LY and GIST, which is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ALB and TP, recognized as relevant proteins for monitoring nutritional status, was lower in the GST group than in the other two groups, which is consistent with other cancers. Serum CA125 is elevated in a variety of tumors and plays a key role in the diagnosis of gastrointestinal malignancies [ 31 ], but it has not received widespread attention and use in the diagnosis of GIST. Numerous studies have confirmed the correlation between the neutrophil-to-lymphocyte ratio (NLR) in cardiovascular diseases, infections, inflammatory diseases and cancer [ 32 , 33 ], but no study has yet singled out LYM% or a potential association between LY and GIST, which is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CA125 (cancer antigen 125) is a glycoprotein present in the epithelium lining body cavities and is a tumor‐associated antigen which exists in the tissues and serum of epithelial ovarian cancer and several digestive tract carcinomas (Bratei et al, 2023). However, it is not widely used in clinic due to its relatively low specificity (Sui et al, 2023). Therefore, the identification of some novel and noninvasive biomarkers for the early diagnosis of NSCLC is extremely urgently needed.…”
Section: Introductionmentioning
confidence: 99%